An aptasensor for the detection of Mycobacterium tuberculosis secreted immunogenic protein MPT64 in clinical samples towards tuberculosis detection - Marzhan Sypabekova; Kanat Dukenbayev; Anna Tsepke; Akmaral Akisheva; Nurlan Oralbayev; Damira Kanayeva (Scientific Reports (Nature Research, CC BY), 2019)
This work presents experimental results on detection of Mycobacterium tuberculosis secreted protein MPT64 using an interdigitated electrode (IDE) which acts as a platform for capturing an immunogenic protein and an electrochemical impedance spectroscopy (EIS) as a detection technique. The assay involves a special receptor, single stranded DNA (ssDNA) aptamer, which specifically recognizes MPT64 protein. The ssDNA immobilization on IDE was based on a co-adsorbent immobilization at an optimized ratio of a 1/100 HS-(CH₂)₆-OP(O)₂O-(CH₂CH₂O)₆-5′-TTTTT-aptamer-3′/6-mercaptohexanol. The optimal sample incubation time required for a signal generation on an aptamer modified IDE was found to be at a range of 15–20 min. Atomic Force Microscopy (AFM) results confirmed a possible formation of an aptamer–MPT64 complex with a 20 nm roughness on the IDE surface vs. 4.5 nm roughness for the IDE modified with the aptamer only. A limit of detection for the EIS aptasensor based on an IDE for the detection of MPT64 in measurement buffer was 4.1 fM. The developed aptasensor was evaluated on both serum and sputum clinical samples from the same TB (–) and TB (+) patients having a specificity and sensitivity for the sputum sample analysis 100% and 76.47%, respectively, and for the serum sample analysis 100% and 88.24%, respectively. The developed aptasensor presents a sensitive method for the TB diagnosis with the fast detection time.
Keywords: Mycobacterium tuberculosis; MPT64 antigen; aptasensor; electrochemical impedance spectroscopy; interdigitated electrode; point-of-care TB diagnosis; type of access: open access